A Study on International Students’ Preferences to Work in Malaysia upon Graduation - Dai, Hairong (2014)
In recent years, more and more people prefer to study abroad. Based on different reasons, some of the knowledge workers which are the overseas students prefer to work in another country after graduation. However, talents are very important for a country, and a lot countries are offering good conditions in order to attract overseas students to return. As we know, Malaysia is a multinational country, and its population is composed of people from all over the world. They have different religions, beliefs and customs. Different reasons attract people from different countries come to Malaysia and settle down in this country. Since 2010, Malaysia proposed an Economic Transformation Programme (ETP) project, which is a good opportunity for all the international students. As for Malaysia government, they need a lot of talents in the process of developing economy. Overseas students is a burgeoning group, when they face the choice of going home or staying in the host country, they will be influenced by different factors to make the decision. Such as the demands of labor market, the culture, and the society. For Malaysia’s international students, to figure out which factors will influence students’ preferences to work in Malaysia is very important for the government. The objective of the research will be analyzed based on the questionnaire and the data that collecting from international students, and factors influencing international students’ preferences to work in Malaysia upon graduation will be found out. The quantitative approach will be used in this research to collect data, and 200 respondents will be chosen to finish the questionnaire. The 5-Point Likert Scale will be used to measure the questionnaire. The data will be analyzed through using SPSS software.